Eco-friendly cellulose-derived transparent carbon nanosheet electrodes. (December 2020) - Son, Su-Young; Yang, Seung-Lyeol; Lee, Sungho; Na, Seok-In; Joh, Han-Ik
Graphical abstract: Highlights: Carbon nanosheets (CNSs) were successfully fabricated by an eco-friendly cellulose/ N-methylmorpholine -N- oxide precursor. Cellulose-derived CNSs were composed of over 99 % C and a small amount of O (∼1 %). The sheet resistance and transmittance of CNSs could be easily adjusted by controlling the cellulose concentration. The CNSs were directly applied as a transparent electrode material in organic photovoltaics without any complex processes. Abstract: In this study, we fabricated carbon nanosheets (CNSs) using an eco-friendly cellulose precursor. Various properties such as the electrical and optical properties of the cellulose-based CNS could be easily adjusted by controlling the precursor concentration. In addition, the CNS was directly applied as a transparent electrode (TE) material in an organic photovoltaic without any additional process, and the device exhibited the highest power conversion efficiency of ∼ 1.84 %. The cellulose-based CNS is expected to have practical applications as a TE material for various electronic devices.